Developing Model of Generosity Participatory Nursing among Cataract Surgery Patients as of Swanson’s Theory, Pathum thani Hospital - ปึกขาว, ละมิตร์; แสนประสาน, เพ็ญจันทร์; หัถรังษี, กาญจนา (Journal of Health Science of Thailand, 2021)
The objective of this research was to (1) study the situation and the nursing desire of cataract surgery patients, (2) study the development of a model for nursing among cataract surgery patients, and (3) to study the outcomes of the nursing model. It was conducted from July 2019 to February 2020. Donabedian conceptual frame work and Swanson’s generosity theory were applied in the study. The sample consisted of 2 groups: (1) 55 ophthalmologists, nurses, pharmacists, patient and caregivers, and (2) 90 nurses, patients, and caregivers. Data collected from the first group through in-depth interviewed as well as the study of statistics and patient medical records; and were analyzed by using content analysis. For the second group, data were collected through questionnaires and the observation on the utilization of study tools: (a) Swanson’s generosity practice guidelines of cataract surgery patients, (b) a video clip of eye wiping, eye drop, applied eye ointment and patient self–conducting at OPD IPD and the operating room, and (c) brochures for post-cataract surgery. Quantitative data were analyzed by using descriptive statistics and paired t-test. It was found that after the model implementation, the scores on knowledge, skills, behaviours, and satisfaction among practice nurses, patients, and care givers significantly increased (p<0.05). There was no post-operative infection. There were 5 factors in the model: (1) structural factor such as personnel, learning, training, practical guidelines development, production training media, of creating of instructional media; (2) the 5 nursing components: knowing patient, being with patient, doing for patient, enabling patient and maintaining believe; (3) outcome factor including the achievement of knowledge, skills, behaviours and satisfaction of nurses, patients and care givers which indicated significant improvement (p<0.05); (4) zero infected cases rate; and (5) high evaluation scores on every part of the model, and 91.5% of the variables were exceeding the standard of AGREE 2 evaluation. Thus, the model could be widely disseminated in order to mprove efficiency of the cataract surgical care.